Performing Repetitions to Failure in Lower-Limb Single-Joint Exercise Does Not Reduce Countermovement Jump Performance in Trained Male Adults - Costa, Bruna (J Hum Kinet, 2021)
Performing repetitions to failure (RF) is a strategy that might acutely reduce neuromuscular performance, as well as increase the rating of perceived exertion (RPE) and the internal training load (ITL) during and after a resistance training (RT) session. Thus, this study aimed to analyze the acute effects of RF or repetitions not to failure (RNF) on countermovement jump (CMJ) performance and the ITL in trained male adults. Eleven men performed two experimental protocols in randomized order (RF vs. RNF). Under the RF condition, participants performed three sets of the leg extension exercise using 100% of the 10RM load and rest intervals of 180-s between sets. Under the RNF condition, participants were submitted to six sets of five repetitions with the same intensity and an 80-s rest interval between sets in the same exercise. The CMJ test was analyzed before and following (15-s and 30-min, respectively) each experimental session. The ITL was evaluated by multiplying the RPE and the total session time, 30-min after the protocol. No main effect or interaction time vs. condition was found for CMJ performance (p > 0.05). In contrast, the ITL showed higher values under the RF condition (p = 0.003). Therefore, even though RF-induced a greater ITL, our results suggest that adopting this strategy in one single-joint exercise for the lower limbs does not seem sufficient to reduce CMJ height.